2005
DOI: 10.1253/circj.69.1454
|View full text |Cite
|
Sign up to set email alerts
|

Acute Myocardial Infarction in Young Japanese Adults Clinical Manifestations and In-Hospital Outcome

Abstract: . Of these, the clinical background, risk factors, angiographic findings, acute results of primary percutaneous coronary intervention (PCI) and in-hospital outcomes for 27 young patients <40 (young group), and 338 non-young patients 60≤, <70 years old (non-young group) were retrospectively compared. The young AMI patients were all male. Current smoking, hypercholesterolemia and family history were the most common risk factors in young patients, while hypertension and diabetes mellitus were more prevalent in no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
34
2
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 27 publications
8
34
2
4
Order By: Relevance
“…1,3,4,7,8,16,17) Our study results were in accordance with these previous studies. Although being overweight has not been considered to be a definite risk factor for MI, it has been suggested to be a risk factor for MI in young populations.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…1,3,4,7,8,16,17) Our study results were in accordance with these previous studies. Although being overweight has not been considered to be a definite risk factor for MI, it has been suggested to be a risk factor for MI in young populations.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies reported that the prevalence of Killip I and single vessel disease in young groups was higher than in non-young groups. 1,4,16,17) Our study results were similar to these studies. The dominance of Killip I and single vessel disease may be a reason for the better outcomes in young AMI.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This difference has shown in other studies of IHD were seen less than non-elderly group, too [13]- [15]. In other countries, this is confirmed [16]- [19]. That might be associated with other risk factors which can show a familial distribution, such as smoking, life style, dyslipidemia, or genetic similarities among families.…”
Section: Discussionsupporting
confidence: 50%
“…The AMI-Kyoto Multi-Center Risk Study, a large multicenter observational study in which 16 collaborating hospitals in Kyoto Prefecture have collected demographic, procedural, and outcome data on AMI patients, was established in 2000 in order to analyze this data and establish an emergency hospital network for heart diseases in Kyoto. [5][6][7] The purpose of the present study was therefore to compare clinical backgrounds, in-hospital prognosis, and determinants of in-hospital outcome in primary PCI-treated AMI patients requiring IABP/PCPS with those of primary PCI-treated AMI patients without IABP/PCPS, using data from the AMI-Kyoto Multi-Center Risk Study.…”
Section: Prognostic Predictors Of Ami With Iabp/pcpsmentioning
confidence: 99%